A comparison among tapentadol tamper‐resistant formulations (TRF) and OxyContin® (non‐TRF) in prescription opioid abusers. (13th March 2013) - Vosburg, Suzanne K.; Jones, Jermaine D.; Manubay, Jeanne M.; Ashworth, Judy B.; Shapiro, Douglas Y.; Comer, Sandra D.
Abstract Aims To examine whether tamper‐resistant formulations (TRFs) of tapentadol hydrochloride extended‐release (ER) 50 mg (TAP50) and tapentadol hydrochloride 250 mg (TAP250) could be converted into forms amenable to intranasal (study 1) or intravenous abuse (study 2). Design Randomized, repeated‐measures study designs were employed. A non‐TRF of OxyContin® 40 mg (OXY40) served as a positive control. No drug was taken in either study. Setting The studies took place in an out‐patient setting in New York, NY. Participants Twenty‐five experienced, healthy ER oxycodone abusers participated in each study. Measurements The primary outcome for study 1 was the percentage of participants who indicated that they would snort the tampered tablets, while the primary outcome for study 2 was the percentage yield of active drug in solution. Other descriptive variables, such as time spent manipulating the tablets, were also examined to characterize tampering behaviors more clearly. Findings Tampered TRF tablets were less desirable than the tampered OXY40 tablets. Few individuals were willing to snort the TRF particles (TAP50: 24%, TAP250: 16%; OXY40: 100% P < 0.001). There was less drug extracted from the TAP50 tablet than from the OXY40 tablet (3.52 versus 37.02%, P = 0.008), and no samples from the TAP250 tablets contained analyzable solutions of the drug. It took participants longer to tamper with the TAPs (study 1: TAP50 versus OXY40, P < 0.01; TAP250 versus OXY40, P < 0.01; study 2: TAP250 versus OXY40, P < 0.05). Conclusions Tamper‐resistant formulations of taptentadol (pain relief) tablets do not appear to be well‐liked by individuals who tamper regularly with extended‐release oxycodone tablets. Employing tamper‐resistant technology may be a promising approach towards reducing the abuse potential of tapentadol extended‐release.